Student satisfaction with feedback in a third year Nutrition unit: A strategic approach - Milne, Lisa; McCann, Jennifer; Bolton, Kristy; Savage, Julia; Spence, Alison (Journal of University Teaching and Learning Practice, 2020)
The feedback received by students on assessment tasks is a major source of their dissatisfaction with feedback generally, explaining why models of assessment continue to evolve to prioritise provision of useful feedback. Boud’s notion of sustainable assessment is an example. We argue for conceptualising the sustainability of assessment practices from teachers’ point of view as well. Assessment is a major component of teaching academics’ workloads. The time and effort required to support particular practices should be considered relative to how well these are evidenced to support student learning outcomes and enhance their satisfaction with feedback. We report on a trial of this approach, from the second phase of action research examining student and staff experiences of targeted feedback on a draft assessment in a large, final year Nutrition unit. The aim of our intervention was primarily to improve student satisfaction with the extent to which feedback in the unit assisted them to achieve learning outcomes, but also to support student learning. Our findings indicate that, in some contexts, impactful practices like providing feedback on drafts alone may not enhance student satisfaction with feedback. Reflection on our findings led us to reframe the next phase of the project more strategically, by advocating for collaboration on course-wide, programmatic assessment, as a sustainable teaching practice and to support sustainable assessment. We call for models of assessment in higher education and course and unit evaluation to be strengthened through further research examining the sustainability of assessment practices for academics, relative to learner outcomes.